2016
DOI: 10.1021/acsomega.6b00179
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step Synthesis of W2C Nanoparticle-Dispersed Carbon Electrocatalysts for Hydrogen Evolution Reactions Utilizing Phosphate Groups on Carbon Edge Sites

Abstract: A novel, one-step protocol for the selective synthesis of W 2 C nanoparticles from phosphotungstic acid (H 3 PW 12 O 40 ), a low-cost and commercially available tungsten compound, was developed. The nanoparticles had diameters of 1–50 nm and were dispersed on a carbon substrate. The W 2 C nanoparticles were prepared by a simple operation sequence, involving impregnation of carbon black with H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The confinement formation of carbides on CNT surface was employed by Li and co‐workers to fabricate ultrasmall and phase‐pure W 2 C, which was highly active than the conventional phase of WC due to the greater density of state near the E F . Conventional approaches using gaseous carbon precursors (e.g., CH 4 ) are unable to yield W 2 C as the main product since the relative amount of carbon to tungsten precursor is out of control, and the carbon diffusion through the gas–solid interface into the tungsten lattice proceeds too fast to allow for phase engineering ( Figure a).…”
Section: Supporting Tmcs By Designed Carbonmentioning
confidence: 99%
“…The confinement formation of carbides on CNT surface was employed by Li and co‐workers to fabricate ultrasmall and phase‐pure W 2 C, which was highly active than the conventional phase of WC due to the greater density of state near the E F . Conventional approaches using gaseous carbon precursors (e.g., CH 4 ) are unable to yield W 2 C as the main product since the relative amount of carbon to tungsten precursor is out of control, and the carbon diffusion through the gas–solid interface into the tungsten lattice proceeds too fast to allow for phase engineering ( Figure a).…”
Section: Supporting Tmcs By Designed Carbonmentioning
confidence: 99%
“…In addition, attaching Mo 2 C and W 2 C to a carbon matrix has been shown to produce high-rate charge transfer properties during HER and to alleviate surface aggregation (Pan et al, 2014; Youn et al, 2014; Wu et al, 2016). Previous reports suggested that the HER electrocatalytic performance of Mo 2 C- and W 2 C-based catalysts mainly results from the morphology (Ang et al, 2016; Ishii et al, 2016; Peng et al, 2017), crystalline phases (Wan et al, 2014; Lin et al, 2017), and composition (Yu et al, 2018; Zhang et al, 2018) of the catalysts and the synthetic protocol. However, the critical challenge is to design and develop carbide-based catalysts with comparable catalytic performance to Pt for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Different methodologies have been used to prepare Mo 2 C and its hybrids for HER applications (Pu et al, 2016; Kou et al, 2018; Liang et al, 2019). Tungsten carbides can exist in different phases, such as WC, metastable W 2 C, and WC 1−x , but during the last decade, most researchers have exclusively focused on the WC phase instead of the W 2 C phase (Neylon et al, 1999; Ishii et al, 2016). W/WC synthesized by Kou et al (2019) showed an overpotential of 159 mV @ 10 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…W‐C materials have two main phases: WC and W 2 C. Numerous studies have reported the preparation of WC and WC‐W 2 C 21‐24 . Nevertheless, only a few studies have reported the preparation of W 2 C 25,26 . All the reported processes have limitations, such as high temperatures, complicated processes, dangerous materials, or low‐yield products.…”
Section: Introductionmentioning
confidence: 99%